Sistem Informasi Electronic Medical Record (EMR) Berbasis Web untuk Meningkatkan Kualitas Hasil Diagnosa Penyakit Pasien - Aryani, Reni; Weni, Indra; Saputra, Edi (Prodi Sistem Informasi FST Universitas Jambi, 2018)
Paper base record medical record system has been widely used in various health care centers. The system is considered to be no longer reliable in handling medical data, because it causes losses such as easily lost, damaged, difficult to search, hard to read, increasing storage space requirements, excessive activity, and the presentation of information does not make it easier for doctors to diagnose patients based on medical data previous patients. So we need a new system more effective and efficient, both in the use of time, energy, and facilities. Electronic Medical Record (EMR) is not a new system in documentation of patient medical records. Case study taken in this research is Regional General Hospital (RSUD) Raden Mattaher Jambi. This study aims to produce EMR system design to improve the quality of patient diagnosis, so that medical mistakes can be prevented, patient data can be accessed directly, can be traced easily, and can provide protection for patient diagnosis more accurate.